What We Can Learn From Studying The Past: The Wonderful Usefulness of History in Educational Research - Westberg, Johannes (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2021)
Why should educational researchers study the history of education? This article suggests that this research is of immediate relevance to current issues of education and may therefore serve a wide variety of purposes. The main argument is that history of education offers four vital contributions: a unique methodological expertise that in turn enables historians of education to provide educational research with vital explanations, comparisons, and the ability to analyse the use and abuse of history in contemporary educational policy and debate. In short, history of education is vital to educational research, not despite its historical orientation, but because of it. Consequently, this paper poses a challenge, both for the field of educational research to promote educational historical research, and for historians of education to explore the untapped potential of this sub-discipline.